Bio-stabilisation of slopes: A review - Thakur Kannan; Parihar Niraj Singh; Sood Hemant (E3S Web of Conferences)
Slope stability is essential for mitigating landslides and erosion risks, especially during heavy rainfall. Vegetation significantly enhances slope stability through soil reinforcement and erosion control. Plant roots stabilize the soil matrix, reducing the likelihood of shallow landslides. However, vegetation's impact varies, with different types potentially influencing slope stability differently—some may even worsen instability under specific conditions. Evidence shows that both rigid and flexible vegetation types improve erosion resistance and slope stability, making them a cost-effective stabilization strategy. Plant water uptake increases matric suction and results in drier slopes, further reinforcing the stability. The mechanical effects of roots, which enhance soil cohesion, combined with the hydrological benefits of improved water management, are crucial for maintaining slope integrity. The present research emphasizes the importance of integrating vegetation into slope management strategies to mitigate landslide risks effectively. Additional measures, including geotechnical advancements, policy development, and community involvement, will complement these efforts. Thus, a comprehensive understanding of vegetation's diverse impacts and root structures, alongside advanced numerical analysis methods, is crucial for optimizing vegetation-based slope stabilization and enhancing safety in landslide-prone areas. In this paper, the authors thoroughly examine and review the state-of-the-art slope stability analysis techniques. Different methods of slope stabilization concerning vegetation have been covered such as RAR, Root Morphology and Density Distribution, root tensile strength and biomechanics, Numerical Analysis, and Limit Equilibrium approaches are the categories under which these techniques are divided.